Assessment of the FilmArray® multiplex PCR system and associated meningitis/encephalitis panel in the diagnostic service of a tertiary hospital. Issue 2 (June 2020) - Mostyn, Amanda; Lenihan, Marie; O'Sullivan, Donnchadh; Woods, Sara; O'Hara, Maureen; Powell, James; Power, Lorraine; O'Connell, Nuala H.; Dunne, Colum P.
Summary: Rapid and accurate diagnosis of meningitis/encephalitis (M/E) is essential for successful patient outcomes. The FilmArray® meningitis/encephalitis Panel (MEP) is a multiplexed PCR test for simultaneous, rapid detection of pathogens directly from cerebrospinal fluid (CSF) samples. 94 prospectively collected CSF specimens from patients with clinical suspicion of infective M/E underwent testing for 14 pathogens simultaneously, including Escherichia coli, Haemophilus influenzae, Neisseria meningitidis, and Varicella zoster . MEP demonstrated 95% agreement with current PCR methods, resulting in 16 diagnosed cases of M/E. Typically, the FilmArray® MEP results were delivered within approximately one hour, contrasting with current practices taking up to 5.6 days. Given the significant morbidity and mortality associated with delayed diagnosis of central nervous system infections, the FilmArray® MEP is a useful addition to the diagnostic capabilities of a clinical microbiology department.